Development of Capital Markets and Institutional Investors in Russia : Recent Achievements and Policy Challenges Ahead - Noel, Michel; Kantur, Zeynep; Krasnov, Evgeny; Rutledge, Sue (Washington, DC: World Bank, 2012)
This study reviews the recent developments in capital markets and institutional investors in Russia, and examines the policy challenges ahead for the development of the sector. The analysis covers key impediments for further development and policy challenges for securities markets, in particular legal and regulatory framework, market infrastructure, government bonds, sub-sovereign bonds, corporate bonds, and equities. The analysis also covers key impediments for further development and policy challenges for mutual funds, pension funds, and insurance companies.